Production, Determination of Proximate and Essential Minerals of Tembakul Fish Flour (Boleophthalmus Sp.) with Variations of Processing Methods - Warsidah - Warsidah; Titi Muhartati; Dwi Iman Prayitno (Department of Chemistry Faculty of Science and Technology Walisongo, 2021)
The Tembakul fish (Mudskipper) is one of the unique fauna resembling amphibian fish that can adapt to two different natural conditions. Boleopthalmus sp is one of three types of Mudskipper that inhabit the mangrove ecosystem in Mempawah. The purpose of this study was to produce fishmeal from Mudskipper Boleopthalmus sp and determine the nutritional content in the form of proximate and essential minerals based on variations in drying treatment before the flouring process. The study was carried out in November-February 2021. Samples were obtained by collecting randomly the Mempawah mangrove area and processed with five different treatments or preparations for flour processing, namely drying with salt, drying without salt, frying with oil, frying without oil, and drying with oven. Nutrient content in the form of proximate in fresh Boleopthalmus sp is fat (0.1 %), protein (20.67 %), water (81.02 %) and ash (1.69%), with phosphorus mineral content (2.06 %), calcium (1.20 %) and iron (259.16 ppm). From these five preparations for processing the fishmeal, it showed that fishmeal was processed by drying without salt before being floured with the flour yield (20 %), fat content (2.18 %), protein content (68.7%), moisture content (15.27 %), and ash content (9.17 %).